Gender Equality in Prenuptial Agreements from a Contemporary Islamic Family Law Perspective - Fatimatuz Zahroni; Bashori Alwi; Adam Adesina Muhammad-Lawal (Yayasan Lembaga Studi Makwa, 2026)
This study examines the role of prenuptial agreements in promoting gender equality within the framework of contemporary Islamic family law. The research aims to analyze the legal basis and practical relevance of prenuptial agreements as instruments for balancing the rights and obligations of spouses in marriage. This study employs normative legal research using statutory, conceptual, and comparative approaches. The data consist of Islamic legal sources, family law regulations, judicial decisions, and contemporary scholarly literature on gender justice and Islamic family law. The findings reveal that prenuptial agreements are not merely contractual arrangements concerning property ownership but also legal mechanisms that provide greater certainty, transparency, and protection for both spouses. Contemporary Islamic family law increasingly recognizes contractual autonomy, provided that the agreed terms do not contradict Islamic principles, public order, or morality. The study further shows that prenuptial agreements may contribute to gender equality by protecting women’s economic interests, clarifying marital responsibilities, and minimizing disputes arising from unequal bargaining positions within marriage. Their legitimacy can be justified through the principles of mutual consent, contractual freedom, ʿadl (justice), and maṣlaḥah (public benefit). The study concludes that prenuptial agreements constitute a legitimate legal instrument capable of supporting gender equality while remaining consistent with the objectives of contemporary Islamic family law. This study contributes to the literature on Islamic family law reform by offering a gender-sensitive interpretation of prenuptial agreements and highlighting their potential to strengthen equitable marital relations in contemporary Muslim societies.